Germline DNA Damage Repair Gene Alterations in Patients with Metachronous Breast and Colorectal Cancer - Villacis, Rolando André Rios; Côrtes, Luiza [UNESP]; Basso, Tatiane Ramos; do Canto, Luisa Matos; Souza, Jeferson Santos; Aagaard, Mads Malik; da Cruz Formiga, Maria Nirvana; Aguiar, Samuel; Achatz, Maria Isabel; Rogatto, Silvia Regina [UNESP] (MDPI, 2024)
A hereditary component of breast (BC) and colorectal cancer (CRC) has been described in approximately one-third of these tumor types. BC patients have an increased risk of developing CRC as a second primary tumor and vice versa. Germline genomic variants (NextSeq550, Illumina) were investigated in 24 unrelated BC and/or CRC patients and 7 relatives from 3 index patients. Fifty-six pathogenic or likely pathogenic variants were identified in 19 of 24 patients. We detected single-nucleotide variants (SNVs) in CRC predisposition genes (MLH1 and MUTYH) and other promising candidates (CDK5RAP3, MAD1L1, NOS3, and POLM). Eighteen patients presented SNVs or copy number variants (CNVs) in DNA damage repair genes. We also identified SNVs recently associated with BC or CRC predisposition (PABPC1, TYRO3, MAP3K1, SLC15A4, and LAMA1). The PABPC1c.1255C>T variant was detected in nine unrelated patients. Each patient presented at least one SNV/CNV in a candidate gene, and most had alterations in more than one gene, reinforcing a polygenic model for BC/CRC predisposition. A significant fraction of BC/CRC patients with a family history of these tumors harbored deleterious germline variants in DNA repair genes. Our findings can lead to strategies to improve the diagnosis, genetic counseling, and treatment of patients and their relatives.
Keywords: breast cancer; cancer predisposition; colorectal cancer; germline variants; hereditary cancer; whole exome sequencing